Enhancing Jumantara Dance Learning: Exploring the Integration of Video into Dance - Musfita Eka Prehantini; Herry Widyastono; Fatma Sukmawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
Learning dance should be accessible and easy for anyone. However, the reality is that many students still need help in learning detail technique dances, for instance the Jumantara dance. One of the contributing factors is the continued use of conventional teaching methods by dance instructors, which primarily rely on imitation and repetitive practice. This traditional approach often poses obstacles to effective dance learning. Data interviews showed three key factors that were identified as causing difficulties in learning the Jumantara dance establishing a feeling of rhythm, expressing the dance's soul, and honing movement methods. Therefore, his study explores how video technology can enhance dance learning methods. This study was treated as a qualitative approach. Our participants were from one of the villages in Indonesia that learned and practiced the Jumantara dance. The data were collected through incorporated observation, document study, interviews, and field notes. The findings of this study demonstrated that video technology can effectively support dance practice in studios. The benefits of developing learning media through this video can minimize the level of technical errors regarding the variety of movements so that it can improve students' ability to express themselves both in motion, rhythm and appreciation of the dance..